Noise Levels and Comfort Levels of Populations Living Around Mistar Cokrokusumo Bangkal District - Sapwandi, Rully; Junaidi, Junaidi; Ali As, Zulfikar; Pahruddin, Muhammad (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Today, many houses are located on the edge of highways, potentially exposing these homes to additional noise from the traffic flow. This study aims to determine the relationship between noise levels and the comfort levels of residential homes in the Bangkal sub-district. This observational study, which has a cross-sectional design, includes 12 sample points for noise measurement and 77 houses directly adjacent to the road for comfort level sampling. Noise levels were measured using a sound level meter, while traffic density was measured using a compass and counter. The relationship between the two variables was analyzed using the Spearman correlation test. Results showed that the volume of traffic flow ranged from 334 pcu/hour to 402 pcu/hour. The highest noise level was recorded at TS-7 (65.7 dBA) and the lowest at TS-9 (61.7 dBA). According to the South Kalimantan governor's regulation number 53 of 2007, all 12 sample points of noise measurement exceed the quality standard. The average correlation between noise level and comfort level indicated that 88% of households reported being less comfortable, 12% felt uncomfortable, and none felt comfortable. Houses can reduce road traffic noise by installing thick curtains on their windows and doors, planting trees and ornamental plants in pots, and constructing artificial walls.